Analisis Gaya Kepemimpinan dalam Meningkatkan Kinerja Karyawan Kantor Pusat PT. Bank Lampung - Suryani Suryani; Melan Susanty; Dewi Aya Sofia (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2022)
The aims of this study was to determine what kind of leadership style is applied by management in improving employee performance at the Head Office of PT. Bank Lampung and whether it has a good impact in improving employee performance, because still many employees at the Head Office of PT. Bank Lampung have not applied discipline to the rules, both written and unwritten rules. The research method used by the researcher is a descriptive method with a qualitative approach. The research was conducted at the Head Office of PT. Bank Lampung with data collection techniques in the form of interviews, observations and documentation. The results of the research showed that the leadership style used by the leaders or managers at the Head Office of PT. Bank Lampung in improving employee discipline is an autocratic leadership style, because the model of this autocratic leadership style further enhances supervision to monitor what activities are carried out by employees. This autocratic leadership style is very effective in increasing the level of employee discipline because the leader can further improve supervision and monitor the activities of subordinates or employees. Employee indiscipline is caused by an incompetent leader so that many employees ignore the rules, both written and unwritten, therefore the leaders or managers at the Head Office of PT. Bank Lampung applies an autocratic leadership style in improving employee discipline, because one of the factors that affect performance is the level of employee discipline. Keywords: leadership style, employee performance